2021
DOI: 10.4236/epe.2021.135010
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Developing Photovoltaics-Powered Vehicles

Abstract: The development of photovoltaics (PV)-powered vehicles are expected to contribute to reduce CO 2 emission of vehicles and create a clean energy society. This paper presents the impact of high-efficiency solar cell modules on reduction in CO 2 emission, charging cost reduction for electric vehicles, and reducing storage capacity of PV-powered electric vehicles. In this paper, the effects of solar cell module efficiency upon driving distance of PV-powered vehicles are also shown. Especially, the potential of Si … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…This comprises autonomy enhancement, electric vehicle deployment, energy saving, economic gain, and CO 2 emission reduction. [525][526][527][528] An extensive overview of the state-of-the-art, recent trends, expected benefits, and perspectives of vehicle-integrated PV (VIPV) is provided in the recent report of the International Energy Agency. [35] As illustrated in Figure 15c, the integration of PV modules in vehicles can be realized on different levels such as 1) roof, 2) engine hood, 3) car sides, and 4) transparent windows.…”
Section: Vehicle-integrated Pvmentioning
confidence: 99%
“…This comprises autonomy enhancement, electric vehicle deployment, energy saving, economic gain, and CO 2 emission reduction. [525][526][527][528] An extensive overview of the state-of-the-art, recent trends, expected benefits, and perspectives of vehicle-integrated PV (VIPV) is provided in the recent report of the International Energy Agency. [35] As illustrated in Figure 15c, the integration of PV modules in vehicles can be realized on different levels such as 1) roof, 2) engine hood, 3) car sides, and 4) transparent windows.…”
Section: Vehicle-integrated Pvmentioning
confidence: 99%
“…We then analyzed the effects of the introduction of high‐efficiency solar cell modules as a VIPV into EVs upon reduction in CO 2 emission by using our anlytical procedure reported in our previous article. [ 16 ] The analyzed results show the effectiveness of high‐efficiency solar cell modules for reduction in CO 2 emission of EVs. [ 16 ] For example, a reduction in CO 2‐e emission is 32.2 g‐CO 2 km −1 for a VIPV module with a conversion efficiency of 40% and $18.6 CO 2−e km −1 for a module with that of 20% in the case of the EM of 10 km kWh −1 .…”
Section: Analysis For Cost Target Of Vipv Modulesmentioning
confidence: 99%
“…1) Regarding module temperature of VIPV, necessity of preventing from temperature rise of VIPV modules and effectiveness of developing high-performance solar cell modules with good temperature coefficient is shown in our recent article. [32] 2) The effects of partial shading upon VIPV modules have been studied by Ota et al [33] The shading of the VIPV is reported [32] to be dependent on the sun's attitude, climate condition, and location; shading objects such as buildings, houses, trees, poles, and others; driving and parking conditions. It was confirmed by previous studies [34,35] that more power was generated under a shadow covering the long side of the PV strings than under a shadow covering the short side of the PV strings because the voltage of optimal operating point of PV module changes less.…”
Section: Comments On the Effects Of The Other Parameters Upon Output ...mentioning
confidence: 99%